Needs Analysis of Implementation of The Mentoring Program for Fundamental Physics 1 Lectures to Support Student Learning Independent - Taqwa, Muhammad Reyza Arief; Nahadi, Nahadi; Sriyati, Siti (Radiasi : Jurnal Berkala Pendidikan Fisika, 2024)
This research uses a descriptive method and aims to analyze the need for a mentoring program in the Fundamental Physics I course. The research was conducted on 64 students (32 students had participated in the mentoring program for one semester, and 32 students did not participate in the mentoring program), 2 lecturers, and 4 tutors. Data were obtained from documents of students' final exam scores, interviews, and surveys. The results showed that (1) the final exam scores of students who participated in the mentoring program were better and significantly different from the class that did not participate in the mentoring program, (2) students who participated in the mentoring program gave a positive response to the program, and (3) students who did not participate in the mentoring program felt that they experienced many difficulties in Fundamental Physics I lectures and felt that the mentoring program was necessary.